Legal Protection Of Personal Data According To Financial Services Authority Regulation - Lidwina Savira Nurulhaq; Nirwan Junus; Mellisa Towadi (Estudiante Law Journal, 2023)
the purpose of this study is to determine the legal protection of personal data of bank customers according to Law No. 8 of 1999 on Consumer Protection and how the implementation of the Financial Services Authority (OJK) Regulation No. 12/PJOK.03/2021.  The method used is using sociological juridical research method, using a descriptive qualitative research approach and interactive analysis techniques. The result of this research is that it arises because the issue of data protection and customer information in Indonesia has become a new problem in the banking world. On the other hand, adequate forms of protection for a customer's privacy rights have not been implemented into legal instruments. Similarly, the existence of various laws (UU) that have the authority to manage one's data and information, are not given limits to avoid violations that result in unprotected data and information of a person.